Dual role of BdMUTE during stomatal development in the model grass Brachypodium distachyon - Spiegelhalder, Roxane; Berg, Lea; Nunes, Tiago D. G.; Dörr, Melanie; Jesenofsky, Barbara; Lindner, Heike; Raissig, Michael Thomas (Development, 2024)
Grasses form morphologically derived, four-celled stomata, where two dumbbell-shaped guard cells (GCs) are flanked by two lateral subsidiary cells (SCs). This innovative form enables rapid opening and closing kinetics and efficient plant-atmosphere gas exchange. The mobile bHLH transcription factor MUTE is required for SC formation in grasses. Yet whether and how MUTE also regulates GC development and whether MUTE mobility is required for SC recruitment is unclear. Here, we transgenically impaired BdMUTE mobility from GC to SC precursors in the emerging model grass Brachypodium distachyon. Our data indicate that reduced BdMUTE mobility severely affected the spatiotemporal coordination of GC and SC development. Furthermore, although BdMUTE has a cell-autonomous role in GC division orientation, complete dumbbell morphogenesis of GCs required SC recruitment. Finally, leaf-level gas exchange measurements showed that dosage-dependent complementation of the four-celled grass morphology was mirrored in a gradual physiological complementation of stomatal kinetics. Together, our work revealed a dual role of grass MUTE in regulating GC division orientation and SC recruitment, which in turn is required for GC morphogenesis and the rapid kinetics of grass stomata.